Validation of Pore-Scale Simulations of Hydrodynamic Dispersion in Random Sphere Packings (Communications in Computational Physics, 2020)
We employ the lattice Boltzmann method and random walk particle tracking to simulate the time evolution of hydrodynamic dispersion in bulk, random, monodisperse, hard-sphere packings with bed porosities (interparticle void volume fractions) between the random-close and the random-loose packing limit. Using Jodrey-Tory and Monte Carlo-based algorithms and a systematic variation of the packing protocols we generate a portfolio of packings, whose microstructures differ in their degree of heterogeneity (DoH). Because the DoH quantifies the heterogeneity of the voidspace distribution in a packing, the asymptotic longitudinal dispersion coefficient calculated for the packings increases with the packings' DoH. We investigate the influenceof packing length (up to 150 dp, where dp is the sphere diameter) and grid resolution(up to 90 nodes per dp) on the simulated hydrodynamic dispersion coefficient, anddemonstrate that the chosen packing dimensions of 10 dp×10 dp×70 dp and the employed grid resolution of 60 nodes per dp are sufficient to observe asymptotic behaviorof the dispersion coefficient and to minimize finite size effects. Asymptotic values ofthe dispersion coefficients calculated for the generated packings are compared withsimulated as well as experimental data from the literature and yield good to excellentagreement.